2023
DOI: 10.3390/ijms241713572
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Angiogenesis in HUVECs Preconditioned with Media from Adipocytes Differentiated from Lipedema Adipose Stem Cells In Vitro

Sara Al-Ghadban,
Samantha G. Walczak,
Spencer U. Isern
et al.

Abstract: Lipedema is a connective tissue disorder characterized by increased dilated blood vessels (angiogenesis), inflammation, and fibrosis of the subcutaneous adipose tissue. This project aims to gain insights into the angiogenic processes in lipedema using human umbilical vein endothelial cells (HUVECs) as an in vitro model. HUVECs were cultured in conditioned media (CM) collected from healthy (non-lipedema, AQH) and lipedema adipocytes (AQL). The impacts on the expression levels of multiple endothelial and angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The study demonstrated how co-culturing BCa cells with human adipocytes heightened the invasiveness of cancer cells through increased secretion of CCL5, suggesting that inhibiting CCL5 in the adipose microenvironment could be a promising strategy to curb highly malignant TNBC ( D’Esposito et al, 2016 ). Moreover, adipocytes have emerged as key players in vascular remodeling and angiogenesis, contributing significantly to the regulation of angiogenesis through the secretion of angiogenic cytokines like VEGF and angiopoietin ( Al-Ghadban et al, 2023 ).…”
Section: Contributions Of Adipocytes To Breast Cancer Pathogenesis An...mentioning
confidence: 99%
“…The study demonstrated how co-culturing BCa cells with human adipocytes heightened the invasiveness of cancer cells through increased secretion of CCL5, suggesting that inhibiting CCL5 in the adipose microenvironment could be a promising strategy to curb highly malignant TNBC ( D’Esposito et al, 2016 ). Moreover, adipocytes have emerged as key players in vascular remodeling and angiogenesis, contributing significantly to the regulation of angiogenesis through the secretion of angiogenic cytokines like VEGF and angiopoietin ( Al-Ghadban et al, 2023 ).…”
Section: Contributions Of Adipocytes To Breast Cancer Pathogenesis An...mentioning
confidence: 99%
“…Liposuction is the most effective treatment for decreasing fibrotic lipedema and fat, thereby improving mobility, which is essential for the quality of life of affected women [6][7][8]. While the etiology of lipedema remains unknown, hormones, genetic factors, inflammation, leaky dilated blood, and lymphatic vessels all contribute to the pathogenesis of lipedema [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, ERβ KO mice have shown no change in body weight or fat distribution compared to wild-type mice [18,20]. Estrogen also regulates leptin and lipoprotein lipase genes (LPL) [21] and increases angiogenesis and vascular endothelial growth factor (VEGF) expression [22], a phenomenon observed in the SAT of lipedema patients [9,10,23]. The G protein-coupled estrogen receptor, GPER, has been implicated in regulating body weight, metabolism, inflammation, and pain [16,24,25].…”
Section: Introductionmentioning
confidence: 99%